Comparative Analysis of the Mitochondrial Genome of Galatheanthemum sp. MT-2020 (Actiniaria Galatheanthemidae) From a Depth of 9,462 m at the Mariana Trench - Shi, Mengke; Qi, Li; He, Li-Sheng (Frontiers in Genetics, 2022)
The hadal zone, which represents the deepest marine habitat on Earth (6,000–11,000 m), is a harsh environment mainly characterized by extremely high hydrostatic pressure, and this habitat is believed to have a high degree of endemism. The deep-sea anemone family Galatheanthemidae comprises two valid species exclusively from the hadal; however, no other information about this family is currently available. In the present study, a sea anemone was collected from a depth of 9,462 m at the Mariana Trench and was defined as Galatheanthemum sp. MT-2020 (Actiniaria Galatheanthemidae). The mitochondrial genome of Galatheanthemum sp. MT-2020 was circular, was 16,633 bp in length, and contained two ribosomal RNA genes, 13 protein-coding genes and two transfer RNA genes. The order of the genes of Galatheanthemum sp. MT-2020 was identical to that of the majority of the species of the order Actiniaria. The value of the AT-skew was the lowest in the whole mitochondrial genome, with a positive GC skew value for the atp8 gene, while other species, except Antholoba achates, had the negative values of the GC skew. Galatheanthemum sp. MT-2020 was clustered with another abyssal species, Paraphelliactis xishaensis, in the phylogenetic tree, and these species diverged in the early Jurassic approximately 200 Mya from the shallow-sea species. The usage ratio of valine, which is one of the five amino acids with the strongest barophilic properties, in the mitochondrial genomes of the two abyssal species was significantly higher than that in other species with habitats above the depth of 3,000 m. The ω (dN/dS) ratio of the genomes was 2.45-fold higher than that of the shallow-sea species, indicating a slower evolutionary rate. Overall, the present study is the first to provide a complete mitogenome of sea anemones from the hadal and reveal some characteristics that may be associated with adaptation to an extreme environment.